ANALISIS PELAKSANAAN KEBIJAKAN PENANGANAN COVID-19 OLEH DESA TERHADAP KEBERADAAN KASUS COVID-19 DI KABUPATEN MAGELANG JAWA TENGAH - Dwi Endah Kurniasih; Venny Vidayanti; Afrezah Afrezah; Rianti Alma Sari Tanne; Agus Widodo; Roy Martfianto (Jurnal Inovasi Penelitian, 2022)
To suppress the rate of encroachment of cases, the Magelang Regency local government formulates a policy for handling covid 19 by referring to the national policy for the acceleration of handling COVID-19. The purpose of the study was to determine the implementation of the Covid 19 handling policy by the village on the presence of Covid 19 cases in Magelang Regency, Central Java. This study is an analytical study using a village readiness survey in handling covid 19 in Magelang Regency in 2020. The research design is cross sectional. The total number of samples from all villages is 372 registered in the survey data for handling covid 19, the Regional Development Planning Agency of Magelang Regency in 2020. The analysis used was univariate and bivariate analysis used the Kendall's tau_b test. The results of the research, most of the 59% of villages/kelurahan have implemented policies for preventing and handling Covid-19 with the category of being ready to deal with Covid-19, 29% of the category being very ready and 12% towards being ready. There is a very close relationship between village readiness and controlling Covid-19 cases (P value 0.00). This conclusion is that all villages 100% have implemented policies in the prevention and handling of Covid-19.